Seasonal Variation in the Population of Indian Black Ibis Pseudibis papillosa, Inhabiting the Arid Zone of Rajasthan, India - Soni, K.C.; Sharma, A.N.; Soni, V.C. (Our Nature, 2010)
The population of Black ibis (Pseudibis papillosa) inhabiting rural and urban area of Churu city, Rajasthan was seasonally determined by the direct count method. The counting of the Black ibis was made at roosting sites of Churu city (28°15′N and 74°55′E, 286 msl) and it’s out skirts area of 400 km2. Total 35 roosting sites were identified in the study area of which 19 were located in the urban area and 16 in the rural areas. It was found that number was relatively higher from June to August in 2003, 2004 and 2005. However, the number was highest from June 2004 to August 2004 and lowest from June 2006 to August 2006. The maximum number of adult was noticed in the rainy months of every year. A sharp decline in the juvenile population was observed from January 2004 to April 2004. Maximum 17 juvenile birds were observed in the months of May and June 2004 and October 2005 while the minimum 4 juveniles were observed in January 2005. An average 40.08±3.62 and 35.33±4.61 in 2003, 42.5±4.81 and 43.16±8.69 in 2004, 42.16±4.23 and 38.33±4.47 in 2005 and 36.25±3.81 and 34.91±4.52 in 2006 ibises were recorded in rural and urban areas, respectively. The maximum number of ibis i.e. 101 individuals, occurred in the month of June, 2004. But in general, the population remained more or less constant with seasonal variations involving dispersion during the monsoons and aggregation during the winters. The winter season adversely affects the population of Black ibis in the study area because of the non availability of preferential food, particularly insects. Key words: Seasonal variation, population, Black ibis, arid zone, Rajasthan, India DOI: 10.3126/on.v7i1.2571 Our Nature (2009) 7:193-202